Resonance transition X-rays generated by 800-900 MeV electrons in a periodic Mylar radiator; Physics Letters A; Vol. 174, iss. 1-2 - Kaplin V. V. Valery Viktorovich; Zabaev V. N. Viktor Nikolaevich; Rozum E. I.; Uglov S. R. Sergey Romanovich; Vorobiev S. A. Sergey Aleksandrovich (1993, 1993)
Title screen